Clinicopathological Characteristics and Molecular Analyses of Multifocal Intraductal Papillary Mucinous Neoplasms of the Pancreas - Matthaei, Hanno (2012)
OBJECTIVE: To examine the clinicopathologic features and clonal relationship of multifocal intraductal papillary mucinous neoplasms (IPMNs) of the pancreas. BACKGROUND: Intraductal papillary mucinous neoplasms are increasingly diagnosed cystic precursor lesions of pancreatic cancer. Intraductal papillary mucinous neoplasms can be multifocal and a potential cause of recurrence after partial pancreatectomy. METHODS: Thirty four patients with histologically documented multifocal IPMNs were collected and their clinicopathologic features catalogued. In addition, thirty multifocal IPMNs arising in 13 patients from 3 hospitals were subjected to laser microdissection followed by KRAS pyrosequencing and loss of heterozygosity (LOH) analysis on chromosomes 6q and 17p. Finally, we sought to assess the clonal relationships among multifocal IPMNs. RESULTS: We identified 34 patients with histologically documented multifocal IPMNs. Synchronous IPMNs were present in 29 patients (85%), whereas 5 (15%) developed clinically significant metachronous IPMNs. Six patients (18%) had a history of familial pancreatic cancer. A majority of multifocal IPMNs (86% synchronous, 100% metachronous) were composed of branch duct lesions, and typically demonstrated a gastric-foveolar subtype epithelium with low or intermediate grades of dysplasia. Three synchronous IPMNs (10%) had an associated invasive cancer. Molecular analysis of multiple IPMNs from 13 patients demonstrated nonoverlapping KRAS gene mutations in 8 patients (62%) and discordant LOH profiles in 7 patients (54%); independent genetic alterations were established in 9 of the 13 patients (69%). CONCLUSIONS: The majority of multifocal IPMNs arise independently and exhibit a gastric-foveolar subtype, with low to intermediate dysplasia. These findings underscore the importance of life-long follow-up after resection for an IPMN.